Effects of biodegradable P3HB on the specific growth rate, root length and chlorophyll content of duckweed, Lemna minor - Prochazkova, Petra; Macova, Sabina; Aydin, Secil; Gargosova, Helena Zlamalova; Kalcikova, Gabriela; Kucerik, Jiri (CELL PRESS, 2023)
The extensive production and use of plastics have led to widespread pollution of the environment. As a result, biodegradable polymers (BDPs) are receiving a great deal of attention because they are expected to degrade entirely in the environment. Therefore, in this work, we tested the effect of two fractions (particles <63 mu m and particles from 63 to 125 mu m) of biodegradable poly-3hydroxybutyrate (P3HB) at different concentrations on the specific growth rate, root length, and photosynthetic pigment content of the freshwater plant Lemna minor. Microparticles with similar properties made of polyethylene terephthalate (PET) were also tested for comparison. No adverse effects on the studied parameters were observed for either size fraction; the only effect was the root elongation with increasing P3HB concentration. PET caused statistically significant root elongation only in the highest concentration, but the effect was not as extensive as for P3HB. The development of a biofilm on P3HB particles was observed during the experiment, and the nutrient sorption experiment showed that the sorption capacity of P3HB was greater than PET's. Therefore, depleting the nutrients from the solution could force the plant to increase the root surface area by their elongation. The results suggest that biodegradable microplastics may cause secondary nutrient problems in the aquatic environment due to their biodegradability.
Keywords: Biodegradable plastics; Duckweed; Ecotoxicity; Microbeads; Micro-bioplastics; P3HB; POLYMERS; MICROPLASTICS; NANOPARTICLES; IMPACT; Science & Technology - Other Topics